Research on AI Promoted Apparel Mass Customization (Journal of Fiber Bioengineering and Informatics, 2024)
The traditional apparel industry faces challenges to the quarantine of the global COVID-19 pandemicdramatically. The AI technics provide promising solutions for the apparel industry shift from labour-intensive to technic-intensive for survival. However, there are many open problems on how AI could findits application in mass customization. This paper presents practicable methods, frameworks and thecurial technologies of AI-promoted apparel mass customization. The AI cloud will apply in traditionalknowledge management of customers (KM) with which AI cloud has been trained and make predication oftrends and customer’s preferences and enable personalized AI recommendations. With AI measurementflexible digital research development techniques can automatically generate personalized patterns andvirtual garment prototypes based on different body shapes. By using the RFID label, the AI cloud couldeasily provide quality control, products tracing back in the production process and AI logistics. Thosesolutions and key technologies will benefit the process of apparel industry 4.0.
Keywords: AI Promoted apparel Mass Customization; RFID Technology; AI Knowledge Management; AI pattern making; Flexible Manufacturing